Pathogenicity and Virulence Factors: Article review - Hussein, Yasser Ali; Ahmed, Hind M. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
A rephrasing of the words "pathogenicity" or "virulence" as they relate to invertebrates disease has been suggested in a recently released investigation that questioned their coherence or intelligibility. Examining the meanings of pathogenicity as well as virulence as they apply to invertebrate disease was our objective, along with providing feedback on this work. The words "pathogenicity" or "virulence" are used differently, despite there is a fair amount of agreement in the explanations that have been written in research on invertebrates pathologies all through the course of the field's past times, as well as in allied fields like microbiological or medical. Researchers did not see any lack of transparency and usefulness in the defined criteria. As a result, they advise that the meaning or use of these words follow precedent. Could be more precise, pathogenicity is the circumstance or attribute that renders something pathogenic, the capacity to cause illness, while virulence is the capability of the living thing can cause illness, the level of pathogenicity inside a species and group. Virulence is a phrase which assesses disease transmission, while pathogenicity is a qualitative, "all-or-none" notion.